Adah Isaacs Menken papers - Menken, Adah Isaacs, 1835-1868.
Correspondence, playbills, clippings, and other papers relating to Menken and her career on the stage in the United States and abroad and as a writer. Includes one undated letter written by Menken; other letters relate to her burial in Paris, France.
Actress and author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Burial -- France -- Paris; Theater -- United States -- History -- 19th century; Theater -- Europe -- History -- 19th century; Actresses; Authors